Pengaruh Penjenjangan Karir Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Multisrada Arah Sarana TBK. Bekasi - Ririn Uke Saraswati; Soedjatmoko Soedjatmoko; Adi Suprayoga (Jurnal Riset dan Inovasi Manajemen, 2023)
This research was conducted to determine the influence of career progression and work environment on employee performance at PT. Multisrada Arah Sarana Tbk. Bekasi. Using SPSS Version 25, this analysis uses multiple linear regression which aims to determine the effect of the Independent variable (X) on the Dependent variable (Y). This research involved 170 PT respondents. Multisrada Arah Sarana Tbk. Bekasi from various divisions. The data collection technique is carried out by distributing statement data that has been previously tested for validity and reliability, then the results of the respondents' answers are processed for analysis. The results of the analysis of this research data can be concluded that Career Pathing does not have a significant effect on Employee Performance, while the Work Environment has a significant effect on Employee Performance. However, career progression and work environment simultaneously have a significant effect on PT employee performance. Multisrada Arah Sarana Tbk. Bekasi.